Management of COVID-19 associated coagulopathy in critically ill patients and the risk of acquired von willebrand syndrome - Hiroyasu Ishikura; Yuhei Irie; Maiko Nakashio; Junichi Maruyama; Yoshihiko Nakamura; Takahiro Yamagaito; Maho Yoshida; Hiroki Hatomoto; Shintaro Yamasaki; Kota Hoshino (Scientific Reports)
Abstract This study investigated the interplay between thrombosis and hemorrhage in critically ill COVID-19 patients, particularly those on extracorporeal membrane oxygenation (ECMO). Forty-three mechanically ventilated patients were divided into ECMO (n = 22) and non-ECMO (n = 21) groups. Thrombotic events occurred similarly in both groups (22.7% in ECMO, 28.6% in non-ECMO), both higher than the approximately 5% observed in patients hospitalized with viral respiratory illnesses other than COVID-19. However, bleeding events were significantly more frequent in the ECMO group (72.7%) compared to the non-ECMO group (14.3%) (P < 0.01). ECMO patients showed decreased platelet counts, fibrinogen, von Willebrand factor (VWF) activity using a ristocetin cofactor (VWF: RCo) assay, and developed acquired von Willebrand syndrome (AvWS) (VWF: RCo/VWF antigen (Ag) ratio < 0.7), along with increased D-dimer and lower high-molecular-weight VWF multimers. In contrast, the non-ECMO group showed no significant changes in platelet counts, fibrinogen, VWF: RCo, or D-dimer. Over time, both VWF: Ag and VWF: RCo increased significantly in both groups, but the VWF: RCo/VWF: Ag ratio remained above 0.7, and high-molecular-weight VWF multimers did not change significantly. These findings emphasize the need for vigilance regarding thrombotic and hemorrhagic complications, particularly in ECMO patients, where ECMO-induced shear stress may lead to AvWS, necessitating monitoring of VWF: Ag and VWF: RCo.